2016
DOI: 10.1051/ijmqe/2016017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indices for the measurement of quality in health systems

Abstract: Abstract. In recent decades different numeric indicators and methods have been used to qualify structured index that express health service components quality performance. The first step of this work is the definition of a model of the system under examination in order to define its measurable constituent entities (dimensions). Among the common measured clinical parameters, a robust metrics, characterizing the constituent entities and the best opportunity tools for the characterization of the results, have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Statistical process control (SPC) techniques have played an efficacious role in monitoring hospital performance such as mortality rate, pre and post-operative complications, number of infections in hospital etc. as reported by Finison et al [5], Finison and Finison [6], Benneyan [7], Maccarthy and Wasusri [8], Clemente et al [9]. The concept of SPC was given by the Walter A Shewhart in order to improve the industrial manufacturing processes.…”
Section: Statistical Process Controlmentioning
confidence: 95%
“…Statistical process control (SPC) techniques have played an efficacious role in monitoring hospital performance such as mortality rate, pre and post-operative complications, number of infections in hospital etc. as reported by Finison et al [5], Finison and Finison [6], Benneyan [7], Maccarthy and Wasusri [8], Clemente et al [9]. The concept of SPC was given by the Walter A Shewhart in order to improve the industrial manufacturing processes.…”
Section: Statistical Process Controlmentioning
confidence: 95%
“…Rachmania et al [ 16 ] discussed the application of a lot acceptance sampling plan in screening women and concluded that this procedure is useful in deciding the quality level of the indicator. Clemente et al [ 17 ] mentioned the use of statistical process control in the emergency medicine department studying door-to-reperfusion time of myocardial infarction patients. Ray et al [ 18 ] presented a case study in Indonesia on the use of control charts in hospitals.…”
Section: Application Of Statistical Quality Control Tools In Health Carementioning
confidence: 99%
“…Maccarthy & Wasusri, [9]; Clemente et al, [10]; Suman et al, [11]; Wiemken, [12]) and are increasingly being adopted for public health surveillance (Woodall,[13]; Morton et al, [14]; Benneyan, [8]). It is suggested that understanding, monitoring and controlling variation in clinical variables is an important part of clinical practice Glasziou et al [15].…”
Section: Introductionmentioning
confidence: 99%